Tradisi Pembagian Waris di Kecamatan Gunungsari Kabupaten Lombok Barat - Abdullah Abdullah; Akhmad Syahri, Akhmad Syahri (Jurnal Hukum Islam, 2020)
The management of hajj savings currently still raises many problems in relation with, for examples, the management of hajj saving for investment and the transparency of the management as well. Based on the fact, this paper aims to analyse the management of hajj saving in the perspective of sharia agreement law. The method of the study uses normative law using a statutory and conceptual approach. The sources of primary law material were obtained from various laws and regulations, while the secondary law materials were obtained from the publications or scientific articles. The technique of analysis of law material uses the analysis perspective by using logic and reasoning law to answer the issue of the law. The result of the research showed that the hajj saving using deposit agreement (wadi‟ah yad dhamanah) and profit-sharing agreements (mudharabah muthlaqah dan muqayyadah). From those two kinds of agreement, the customers of hajj saving have automatically permitted the Bank to use the hajj saving. However, if the contract that is used is mudharabah muqayyadah, the customers of hajj savings can provide special restriction to the Bank to use and to manage the money in accordance with the agreement of both parties. Therefore, there should be transparency in the management of hajj savings as a form of responsibility of the manager to the customers.